Dual inhibition of phosphoinositide 3-kinases delta and gamma reduces chronic B cell activation and autoantibody production in a mouse model of lupus - Olayinka-Adefemi, Folayemi; Hou, Sen; Marshall, Aaron J. (Frontiers in Immunology, 2023)
Phosphoinositide 3-kinase delta (PI3Kdelta) plays key roles in normal B cell activation and is chronically activated in malignant B cells. Targeting of PI3Kdelta using FDA-approved drugs Idelalisib or Umbralisib has shown efficacy in treatment of multiple B cell malignancies. Duvelisib, an inhibitor targeting both PI3Kdelta and PI3Kgamma (PI3Kd/gi) has also been used for treatment of several leukemias and lymphomas and was suggested to offer potential additional benefits in suppressing T cell and inflammatory responses. Transcriptomics analyses indicated that while most B cell subsets predominantly express PI3Kgamma, plasma cells upregulate PI3Kgamma. We thus assessed whether PI3Kd/gi treatment can impact chronic B cell activation in the context of an autoantibody-mediated disease. Using the TAPP1R218LxTAPP2R211L (TAPP KI) mouse model of lupus-like disease driven by dysregulated PI3K pathway activity, we performed 4 week PI3Kd/gi treatments and found significant reduction in CD86+ B cells, germinal center B cells, follicular helper T cells and plasma cells in multiple tissues. This treatment also significantly attenuated the abnormally elevated serum levels of IgG isotypes observed in this model. The profile of autoantibodies generated was markedly altered by PI3Kd/gi treatment, with significant reductions in IgM and IgG targeting nuclear antigens, matrix proteins and other autoantigens. Kidney pathology was also impacted, with reduced IgG deposition and glomerulonephritis. These results indicate that dual inhibition of PI3Kdelta and PI3Kgamma can target autoreactive B cells and may have therapeutic benefits in autoantibody-mediated disease.